Collaborative control of branching ratio in the O + HO2 → OH + O2 reaction via vibrational and rotational excitation. Issue 3 (19th October 2022) - Chen, Qixin; Hu, Xixi; Xie, Daiqian
Abstract: To understand the effect of different vibrational and rotational modes of reactant to enhance the reactivity of the O + HO2 → OH + O2 reaction, we revisited this important atmospheric reaction. We report here a quasi‐classical trajectory (QCT) study of the reaction dynamics on a recently developed full‐dimensional potential energy surface (PES). Our previous work has indicated that this reaction has two pathways, the H abstraction (HA) channel and the O abstraction (OA) channel, which lead to totally different product energy distribution. In this work, we identified that the vibrational excitation of the OH stretching ( v 1 ) mode of HO2 is the switch of the HA channel at low collision energy; meanwhile, the rotational excitation can also greatly change the branching ratio of the two pathways. With the excitation of v 1 mode, the original negligible HA channel controlled by the tight transition state becomes quite important. This work presents an approach to control the branching ratio via collaboration between vibrational and rotational excitation and will enrich the knowledge of the O + HO2 reaction in atmospheric chemistry and physics. Abstract : The important atmospheric reaction O + HO2 → OH + O2 has two pathways that lead to totally different product energy distribution. The excitation of O–H stretching of the reactant HO2 can open the H abstraction channel at low collision energy. In addition, the rotational excitation of HO2 can significantly increase the branching ratio of the H abstraction channel.